STRUCTURING PEDAGOGICAL CONTENT PRACTICES OF STUDENTS BY SPECIALTY "PRESCHOOL EDUCATION" - R.V. Kondratenko (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the structure of the content of the pedagogical the practice o f the student's - of future tutors I-II courses pedagogical university, direct on the formation of the readiness for the upbringing of responsibility in the preschool children's.